Application of Passive Self-ligating Brackets in Orthodontic Treatment - Jiang, Jin-gang; Guo, Xiao-wei; Han, Ying-shuai; Zhang, Yong-de; Yu, Xiao-yang (Recent Patents on Engineering, 2017)
Background: Malocclusion is a common oral disease. Wearing the lingual or labial straight archwire appliance is an effective treatment method. For the traditional appliance, the bracket is a non self-ligating structure. Orthodontic archwire is fixed by the ligature, so the ligation and removal operation is time-consuming. And the end of the ligation wire may be easy to scratch the oral cavity and the aggregation bacteria. With the continuous development of orthodontic technique, the self-ligating bracket is the development direction for future clinical orthodontic treatment, and has become an advanced research hotspot. Objective: To provide an overview of recent passive self-ligating brackets, and introduce their respective characteristics and development. Method: The recent typical brackets are divided into passive self-ligating bracket, active self-ligating bracket and interactive self-ligating bracket. This paper reviews various representative patents related to passive self-ligating bracket. The structural characteristics and applications of the typical passive selfligating bracket are introduced. Results: The differences of different types of passive self-ligating bracket are compared and analyzed, and the structural characteristics are concluded. The main problems in its development are analyzed, the development trend is foreseen, and the current and future research of the patents on passive self-ligating bracket is discussed. The passive self-ligating bracket, because of its small friction, gentle orthodontic force, discomfort reduction, chair time reduction and excellent oral hygiene maintenance, is recognized and applied by more and more orthodontic doctors. Conclusion: The passive self-ligating bracket has important practical significance. And further improvements are needed in the aspects of structure, cost, use and reliability, bracket base failure of the passive self-ligating bracket, and detachment of locking system from bracket's main structure. More patents on the passive self-ligating bracket should be invented.
Keywords: locking device